miR-155 Predicts Long-Term Mortality in Critically Ill Patients Younger than 65 Years - Frank Tacke; Martina E. Spehlmann; Mihael Vucur; Fabian Benz; Mark Luedde; David Vargas Cardenas; Sanchari Roy; Sven Loosen; Hans-Joerg Hippe; Norbert Frey; Christian Trautwein; Alexander Koch; et al. (Mediators of Inflammation)
Introduction. Alterations in miR-155 serum levels have been described in inflammatory and infectious diseases. Moreover, a role for miR-155 in aging and age-related diseases was recently suggested. We therefore analyzed a potential age-dependent prognostic value of circulating miR-155 as a serum-based marker in critical illness. Methods. Concentrations of circulating miR-155 were determined in 218 critically ill patients and 76 healthy controls. Results. By using qPCR, we demonstrate that miR-155 serum levels are elevated in patients with critical illness when compared to controls. Notably, levels of circulating miR-155 were independent on the severity of disease, the disease etiology, or the presence of sepsis. In the total cohort, miR-155 was not an indicator for patient survival. Intriguingly, when patients were subdivided according to their age upon admission to the ICU into those younger than 65 years, lower levels of miR-155 turned out as a strong marker, indicating patient mortality with a similar accuracy than other markers frequently used to evaluate critically ill patients on a medical ICU. Conclusion. In summary, the data provided within this study suggest an age-specific role of miR-155 as a prognostic biomarker in patients younger than 65 years. Our study is the first to describe an age-dependent miRNA-based prognostic biomarker in human diseases.